Adoption of Financial Technology Innovation and Its Effect on SME Accounting Performance - Sahar Moharram (PT. BATARI EDU CALYA, 2024)
The rapid proliferation of financial technology (fintech) has fundamentally transformed the financial landscape for small and medium enterprises (SMEs) globally, presenting both unprecedented opportunities and significant challenges for accounting practices. This study investigates the adoption of fintech innovation and its consequential effects on SME accounting performance within the Egyptian context. Employing a quantitative research methodology, this investigation examines the determinants of fintech adoption among Egyptian SMEs and evaluates the impact on various dimensions of accounting performance, including financial reporting quality, management accounting practices, and overall organizational performance. The findings reveal that fintech adoption, particularly through digital accounting transformation, artificial intelligence integration, and mobile financial services, significantly enhances accounting practices and contributes to improved financial performance among Egyptian SMEs. The study further identifies critical contextual factors, including firm competitiveness, organizational readiness, and management characteristics, as determinants influencing the adoption level of both fintech solutions and management accounting practices. These results contribute to the growing body of literature on fintech adoption in developing economies and provide practical implications for policymakers, financial institutions, and SME practitioners seeking to leverage technological innovation for enhanced accounting performance.